Determination of the Reliability and Accuracy of the Brix Refractometer for the Detection of Colostrum Quality in Sheep - Mehmet Akköse; Ceyhan Özbeyaz; Sebastien Buczinski; Umutcan Gündoğar; Necmettin Ünal (Veterinary Medicine and Science, 2025)
ABSTRACT This study was aimed at the assessment of the reliability and performance of the Brix refractometer for the determination of colostral IgG concentrations in sheep. A total of 190 colostrum samples were collected from 150 ewes of various breeds. Out of the colostrum samples, 101 were taken at parturition, 10 at 6 h postpartum, 6 at 8 h postpartum, 2 at 10 h postpartum, 65 at 12 h postpartum and 6 at 24 h postpartum. The Brix percentages of the colostrum samples were determined using a Brix refractometer, and the colostral IgG concentrations were measured with the radial immunodiffusion (RID) technique. Correlation coefficients were calculated between the Brix percentages and RID‐IgG values. Receiver operating characteristics (ROC) analyses were performed to determine the optimal Brix thresholds for the prediction of colostral IgG concentrations using <20, <50, <75 and <100 g/L thresholds. The misclassification cost term (MCT) analyses were performed to test the robustness of the Brix thresholds based on the relative costs of misclassifications. The mean IgG concentration and Brix percentage of the ewe colostrum samples were determined as 62.7 g/L and 27.2%, respectively. A high correlation was detected between the colostral RID‐IgG concentrations and Brix percentages (r = 0.83). Brix percentages of ≤25.0%, ≤25.9%, ≤27.5% and ≤31.9% indicated IgG concentrations of <20, <50, <75 and <100 g/L, respectively. The Brix refractometer was demonstrated to be a low‐cost, practical and reliable tool for the determination of colostrum quality in sheep. It is recommended that the four Brix thresholds determined in this study be used strategically in feeding lambs in need of colostral supplementation due to inadequate or poor‐quality colostrum production by their dams.